DFT Calculation on 76 Polychlorophenazines: Their Thermodynamic Function and Implication of Cl Substituted Position. (26th October 2008) - Yu, Hong-Xia; Liu, Hui; Wang, Zun-Yao; Wang, Lian-Sheng
Abstract : Thermodynamic functions, including enthalpy (H θ ) and entropy (S θ ) for 76 polychlorophenazines (PCPZs) in the gas state at 298.15 K and 101.325 kPa, have been calculated using the B3LYP/6-31G ∗ level with Gaussian 03 program, and considered on solvation affects. Total free energy in water (G w ) was calculated with the same program. Based on these data, the isodesmic reactions were designed to calculate the standard formation heat (Δ f H θ ) and standard free energy of formation in water( Δ f G w θ ) . The dependences of these thermodynamic parameters on the numbers and positions of chlorine substitution (N PCS ) were discussed. It is suggested thatS θ,     Δ f H θ, andΔ f G w θ of PCPZs varied greatly withN PCS . Moreover, the values of molar heat capacity at constant pressure (C p, m ) from 200 to 1800 K for PCPZ congeners were calculated using a statistical thermodynamics calculation program based on Gaussian output files, and the temperature-dependence relation ofC p, m was obtained using the least-squares method. In addition, according to the relative magnitude of theirΔ f G w θ, the relative stability order of PCPZ congeners was theoretically proposed.